Combining a DS-DBR laser with QPM-DFG for mid-infrared spectroscopy - Whittaker, K; Ciaffoni, L; Hancock, G; Islam, M; Peverall, R; Ritchie, G (2012)
Studies into the suitability of a novel, widely tunable telecom L-band (1563-1613 nm) digital supermode distributed Bragg reflector (DS-DBR) laser for spectroscopy in the mid-IR are presented. Light from the DS-DBR laser was mixed with 1064 nm radiation in a periodically poled lithium niobate (PPLN) crystal to generate mid-IR light by quasi phase matching difference frequency generation (QPM-DFG). The resultant continuous wave radiation covered the range 3000-3200 cm-1 with powers of up to 2.6 μW. The use of such laser light for spectroscopic applications was illustrated by performing absorption experiments on both narrow-band and broad-band absorbers, namely methane (CH4) and methanethiol (CH3SH). Wavelength modulation spectroscopy (WMS) on CH4 demonstrated that the modulation characteristics of the DS-DBR laser observed in the near-IR were transposed to the mid-IR and yielded a sensitivity of 3.1×10-6 cm-1 Hz-1/2 over a 47 cm path length. In the CH3SH spectrum, the absorption feature at 3040 cm-1 was identified as a potential useful region for monitoring this biomarker in exhaled breath at reduced pressures. © 2012 Springer-Verlag.